Implementing standardized cancer patient pathways (CPPs) - a qualitative study exploring the perspectives of health care professionals - Sara Delilovic; Henna Hasson; Mårten Åhström; Mia von Knorring (BMC, 2019)
Abstract Background Many countries have implemented standardized cancer patient pathways (CPPs) to reduce waiting times in cancer care and to ensure timely and quick diagnosis as well as treatment. Yet, no studies have explored the implementation process as perceived by the health care professionals working in the CPPs. The aim of this study is to explore the experiences of health care professionals (HPCs) involved in the CPPs. Methods A descriptive qualitative design was adopted. Thematic analysis was applied to individual interviews conducted in 2016-2017 with 58 participants working in six different CPPs in Sweden's largest region, covering care for around 2.3 million inhabitants. Results In general, the health care professionals had a positive attitude towards the implementation of the CPPs. Our findings showed that the CPPs require close collaboration, both between and within different health care professional groups and units, something that was not always probable due to differences in resource capacity. Better dissemination to all relevant professionals, better conceptualization, and equivalent opportunities in terms of resources were identified by the respondents as being important yet lacking in practice. The analysis showed possible negative effects of the CPP, such as crowding-out on other patient groups. Conclusion The CPPs were introduced to address challenges with long waiting times and unequal cancer care. By exploring the experiences of health care professionals involved in the implementation of CPPs, our findings show challenges with multi-level coordination and collaboration, policy dissemination, and resource constraints. The analysis also showed that the implementation of CPPs risk being accompanied by unintended effects such as longer waiting times for other patients and patient groups in need of the same health care resources. The results shed light on and contribute to an understanding of the challenges, opportunities and ways forward.